2010
DOI: 10.1103/physrevb.81.075316
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of electrically gated bismuth telluride nanowires

Abstract: We theoretically studied the effect of the perpendicular electric field on the thermoelectric properties of the intrinsic, n−type and p−type bismuth telluride nanowires with the growth direction [110]. The electronic structure and the wave functions were calculated by solving self-consistently the system of the Schrödinger and Poisson equations using the spectral method. The Poisson equation was solved in terms of the Newton -Raphson method within the predictor-corrector approach. The electron -electron exchan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…[1][2][3] Recently both theoretical predictions and experimental investigations have demonstrated that Bi 2 Te 3 is also a topological insulator (TI). [4][5][6] TI is a new state of quantum matter with an insulating bulk gap or gapless edge and current-carrying massless Dirac surface states, and exhibits a rich variety of physical phenomena such as anomalous magneto-electric coupling and Majorana excitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Recently both theoretical predictions and experimental investigations have demonstrated that Bi 2 Te 3 is also a topological insulator (TI). [4][5][6] TI is a new state of quantum matter with an insulating bulk gap or gapless edge and current-carrying massless Dirac surface states, and exhibits a rich variety of physical phenomena such as anomalous magneto-electric coupling and Majorana excitations.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic mail: jxzhong@xtu.edu.cn (J. X. Zhong), xqi@xtu.edu.cn (X. Qi). 3 ) are placed at the heating zone. Before the experiment, the quartz tube is initially pumped down to 33 Torr and flushed several times with Ar gas to remove oxygen residue.…”
Section: Introductionmentioning
confidence: 99%
“…The existing theoretical studies on the thermoelectric devices are mostly based on either the continuum models [11,12,[16][17][18] or the tight-binding methods. [19,20] Continuum models (effective mass approximation) though useful for their simplicity and computational efficiency, cannot capture the details of the atomistic effects that can be present in lowdimensional structures.…”
mentioning
confidence: 99%
“…Compared to other existing fabrication methods, the samples prepared by high pressure sintering method have the following advantages: higher efficiency, lower cost, more suitable for large-scale production, more homogeneous nanocrystalline grain and restraining grain from coarsening during sintering process, etc. In addition, pressure tuning is thought to be one of the ways to improve the TE properties of thermoelectric materials [31]. In our previous research, we prepared Bi 0.5 Sb 1.5 Te 2.7 Se 0.3 bulk samples through high pressure sintering technique together with heat treatment, and found ZT value to increase up to 1.16 at 323 K [30].…”
Section: Introductionmentioning
confidence: 99%